Studies on the Optical Properties and Surface Morphology of Copper Phthalocyanine Thin Films - JOSEPH, BENNY; MENON, C.S. (Asian Journal of Chemistry, 2010)
Vacuum sublimed thin films of copper phthalocyanine (CuPc) at a base pressure of 10-5 m.bar are fabricated using a Hind-Hivac thermal evaporation plant. The films are deposited on to glass substrates at various temperatures 318, 363, 408 and 458K. The optical absorption spectra of these thin films are studied and found that the optical band gap energies of CuPc thin films are highly dependent on the substrate temperatures. The structure and surface morphology of the films deposited on glass substrates of temperatures 303, 363 and 458 K are studied using X-ray diffractograms and scanning electron micrographs, which shows that there is a change in the crystallinity and surface morphology due to change in the substrate temperature. Full width at half maximum (FWHM) intensity of the diffraction peaks is also found reduced with increasing substrate temperatures. The structure and lattice constants are determined. The optical band gap is found increased and then reduced with flake shaped large grains with increase in substrate temperatures. Additional trap levels are also found in films prepared at high substrate temperatures.